Partial purification and characterization of an antimicrobial substance produced by a marine Alteromonas sp. - León, Jorge (2005)
A member of the genus Alteromonas sp. (strain N22.C) isolated from marine neuston and substance-producer which inhibit growth of ichthyopathogenics was characterized phenotipically by means of morphological, physiological and biochemical conventional tests. To determine the chemical nature of the inhibitory substance, raw extracts of supernatans from cultured strains were precipitated with increasing concentrations of Ammonium Sulphate up to 70% and filtered through columns of Sephadex G-25. Assays by Sodium Dodecyl Sulfate–Polyacrylamide Gel Electrophoresis (SDS–PAGE) revealed that the antimicrobial substance is a proteinaceous compound with a molecular mass of approximately 34000 Da, which lacks sugar associated residues of it. Other assays made with raw semipurified fractions extracts of Alteromonas sp N22.C show the wide spectrum of antibiotic activity against pathogenic bacterial strains of fish, mollusks and crustaceans.